STUDI TINGKAT KECEMASAN IBU POST PARTUM TERHADAP KELANCARAN ASI PADA IBU NIFAS HARI KE-5 (DI BPM ASRI DAN POLINDES PERMATA BUNDATUBAN) - Qiftiyah, Mariyatul (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2018)
Anxiety is a natural disturbance of feelings characterized by a feeling of deep and sustained fear or concern. Unclear anxiety can affect the hormone oxytocin mother does not come out. Hormone oxytocin is one of the hormones that play a role in the production of breast milk. Many factors that affect production of ASI include anxiety or stress. The purpose of this research is to know the Level of Anxiety Mother Post Partum's to Smooth ASI On Post Partum Day 5.Design This research use descriptive design, this research consist of two variable that is level of anxiety and smooth of ASI. The population used is all postpartum day 5 who gave birth at BPM Asri and Polindes Permata Bunda Tuban. The samples taken were the 5th day postpartum mothers who met the inclusion criteria of 34 respondents by taking samples using purposive sampling. Data collection techniques are primary data. How to collect data by using questionnaires and interviews are questionnaires on the variable level of anxiety and interviews on variable fluency of ASI. Data analysis using cross table and proportion test.The results of the study of 34 respondents mostly as many as 23 respondents (67.6%) post partum mothers did not experience anxiety, almost half of 10 respondents (29.4%) experienced moderate anxiety, a small part of 1 respondents (2.9%) experienced moderate anxiety , half as many as 17 respondents (50%) experiencing milk is not smooth.From the results of the study showed no anxiety relationship with the smoothness of breast ASI. For that reason should anxiety can affect the smoothness of breast ASI but in this study there is no anxiety relationship with the smoothness of breast ASI, because it could be influenced by other factors such as nutritional intake, age, shape / condition of nipple, family support. Therefore it is expected that health workers provide information on breast milk and encourage husbands and families to continue to provide support, because with the support of the closest people can affect the smoothness of breast milk production and avoid anxiety so as to create a comfortable atmosphere in the family and mother feel comfortable happy